STRATEGI BERSAING MELALUI MANAJEMEN MEREK DAN KEMASAN PRODUK UMKM DESA LANCANG KUNING - Kintani, Eldesia Cahaya; Rowaidah, Rowaidah; Romdoni, Muhammad; Apriyanti, Fhertyna; Putra, Sapriadi (P3M STIE Pembangunan Tanjungpinang, 2025)
Micro, Small and Medium Enterprises (MSMEs) play a very important role in economic growth in Lancang Kuning Village. MSMEs provide a positive value for increasing community income. This is reflected in the increasing number of MSMEs in Lancang Kuning Village. Sorghum is one of the Micro Small Business pilot products with the business name Sorghum Ibu Ririn. But unfortunately, Mrs. Ririn's MSMEs do not have good packaging and packaging labels so they need a change of packaging and attractive packaging labels so that their business can be better known to the outside community. This community service activity was carried out to help Mrs. Ririn's UMKM to improve brand management and product packaging. The methods used in this service activity are survey methods, direct interviews, training, socialization and direct assistance to MSME owners. The survey results show that in Mrs. Ririn's yam chips MSME, the obstacles are not yet having a product label, product packaging that is not appropriate so that it makes the product easily damaged and does not yet have a HALAL certificate. After making packaging innovations and more attractive labels, sales made by the two MSMEs have increased. In addition to experiencing an increase in sales, better product packaging also has a positive impact on the durability of the product itself.